UGPS J194310+183851: an unusual optical and X-ray faint cataclysmic variable?. Issue 4 (21st June 2022) - Morris, C; Maccarone, T J; Lucas, P W; Strader, J; Britt, C T; Miller, N; Swihart, S J; Cooper, W J; Drew, J E; Guo, Z
ABSTRACT: The growing number of multi-epoch optical and infrared sky surveys are uncovering unprecedented numbers of new variable stars, of an increasing number of types. The short interval between observations in adjacent near-infrared filters in the UKIDSS Galactic Plane Survey (UGPS) allows for the discovery of variability on the time-scale of minutes. We report on the nature of one such object, through the use of optical spectroscopy, time series photometry, and targeted X-ray observations. We propose that UGPS J194310.32+183851.8 is a magnetic cataclysmic variable star of novel character, probably featuring a longer than average spin period and an orbital period likely to be shorter than the period gap (i.e. P orb < 2 h). We reason that the star is likely a member of the short-period intermediate-polar subclass that exists below this period boundary, but with the additional feature that system's spectral energy distribution is fainter and redder than other members of the group.